Revealing Medieval Books’ Dirty Little Secrets: Tracing Late-Medieval Use of a Breviary in Turku diocese - Heikkilä, Tuomas; Vikman, Kirsi (Mirator, 2025)
This article examines the liturgical books used in the Turku diocese in the late 15th century, focusing on a Breviary printed by Anton Koberger in 1485. It argues that, based on the significant number of surviving copies in the Turku diocese, Koberger’s Breviary—not the 1488 Missale Aboense—marked the initial step towards liturgical harmonisation in the region through the use of printed books. The article introduces a novel method for quantifying the intensity of use of individual pages by assessing their levels of accumulated dirt. Applied to Koberger’s Breviary, this method offers new insights into the most frequently consulted sections, thereby illuminating the practices surrounding the celebration of the liturgical office in Turku during this period.